Implementasi Strategi Pembelajaran Kontekstual dalam Materi Bangun Datar Sederhana di SD Negeri 1 Mayahan - Suharyono Suharyono; Nur Fajrie (Peneliti.net, 2023)
This research is an ongoing research that seeks to seek informal information regarding the objects studied, this research was carried out at SD Negeri 1 Malyalhaln, Talwalnghaljo District, Kalbupalten Grobogaln/ Based on the results of analysis and analysis of contextual learning in this study, it can be concluded that through the implementation of the Contextual Learning Strategy approach, the results of the mental learning of students at SD Negeri 1 Malwalal, Talwalnghalrjo, Kalbupalten, Grobogal, have increased